Isolation and structure determination of a tetrameric sulfonyl dilithio methandiide in solution based on crystal structure analysis and 6Li/13C NMR spectroscopic data - Vollhardt, Jürgen; Lindner, Hans Jörg; Gais, Hans-Joachim (Beilstein Journal of Organic Chemistry, 2020)
Dilithio sulfonyl methandiides are a synthetically and structurally highly interesting group of functionalized geminal dianions. Although very desirable, knowledge of the structure of dilithio methandiides in solution was lacking up to now. Herein, we describe the isolation and determination of the structure of tetrameric dilithio (trimethylsilyl)(phenylsulfonyl) methandiide in solution and in the crystal. The elucidation of the structure of the tetramer is based on crystal structure analysis and 13C/6Li NMR spectroscopic data. A characteristic feature of the structure of the tetramer is the C2 symmetric C–Li chain, composed of four doubly Li-coordinated dianionic carbon and five Li atoms. Three Li atoms are devoid of a contact to a dianionic C atom. The tetramer, the dianionic C atoms of which undergo fast exchange, is in THF solution in fast equilibrium with a further aggregate, which is stable only at low temperatures.
Keywords: crystal structure; dilithio sulfonyl methandiide; NMR; solution structure; X-ray analysis